1973
DOI: 10.1161/01.cir.47.4.786
|View full text |Cite
|
Sign up to set email alerts
|

Intrarenal Blood Flow in Congestive Heart Failure

Abstract: Intrarenal blood flow distribution was measured by the 133 xenon washout technic in 10 patients with heart disease who were studied at time of left and right heart catheterization. Renal washout curves were analyzed by computer using a weighted least-squares nonlinear regression technic. In three patients with heart disease without edema the compartment I blood flow rates (outer cortex) were not significantly different from those found in nine normal kidney donors. In seven patients wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
12
1

Year Published

1974
1974
1994
1994

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(15 citation statements)
references
References 42 publications
2
12
1
Order By: Relevance
“…Our values for baseline liver "flow" are about twice as high as those reported by others [6,8,19] which could indicate sphere leakage from the intestines. On the other hand, our results for baseline intestinal flow do not deviate from those of earlier studies [16,19]. Therefore, a definite conclusion regarding leakage cannot be drawn.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Our values for baseline liver "flow" are about twice as high as those reported by others [6,8,19] which could indicate sphere leakage from the intestines. On the other hand, our results for baseline intestinal flow do not deviate from those of earlier studies [16,19]. Therefore, a definite conclusion regarding leakage cannot be drawn.…”
Section: Discussioncontrasting
confidence: 99%
“…The lost spheres are trapped in the lung and liver, and a relatively high "flow" value in these organs can be explained by a high level of peripheral shunting or leakage or both. Other workers using 15 gm spheres have reported baseline values for lung "flow" that fit fairly well with ours [6,16,19]. This seems to indicate that general perexperimental leakage of microspheres injected in the baseline situation is not present to a high degree in this experimental model.…”
Section: Discussionsupporting
confidence: 88%
“…2). It has also been shown that in heart failure, intrarenal blood flow is redistributed re sulting in outer cortical ischemia [18]. Nephrons in this region normally excrete a higher fraction of filtered sodium than juxtamedullary nephrons do.…”
Section: Renal Hemodynamics In Heart Failurementioning
confidence: 99%
“…The etiology of the altered fluid balance in CHF can be attributed to both hemodynamic (1,3,5,7) and hormonal factors (4,(8)(9)(10)(11). Evidence has been presented by several investigators that the secretion of antidiuretic hormone (ADH) may be altered during CHF or related disease states (12)(13)(14)(15)(16)(17)(18)(19).…”
Section: Introductionmentioning
confidence: 99%